The type specimens of Calyptratae (Diptera) housed in non-traditional institutions in Argentina - Patitucci, Luciano Damián (2015)
The type material of species of Calyptratae Diptera belonging to Anthomyiidae, Calliphoridae, Fanniidae, Muscidae, Sarcophagidae, and Tachinidae, housed in the collections of non-traditional institutions in Argentina were examined. These collections were included in the recently created “Sistema Nacional de Datos Biológicos” (National Biological Data System). We examined four collections: “Administración Nacional de Laboratorios e Institutos de Salud ‘Dr. Carlos G. Malbrán’” (ANLIS), “Instituto Nacional de Tecnología Agropecuaria, Castelar, Buenos Aires” (INTA), “Instituto Argentino de Investigaciones de las Zonas Áridas” (IADIZA); and “Fundación Félix de Azara” (CFA). Comparison of the original descriptions of these species with the label information revealed the existence of 24 holotypes, 5 lectotypes, 11 syntypes, and 441 paratypes/paralectotypes. Complete information is given for each type, including reference to the original description, label data, and preservation condition.